THE ANALYSIS OF FACTORS THAT AFFECT PROFIT MANAGEMENT IN FOOD SUBSECTOR FOOD AND BEVERAGES COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE 2013 - 2016 PERIOD - Tondang, Yohannes (International Journal of Public Budgeting, Accounting and Finance, 2018)
Theinformation of profit inthe financial statements isthemajor concern to estimate howgood the performance or responsibility of the company management is. When thecompany failsto achieve the expectedprofits, themanagerscan be triggeredto take unhealthy actions in the company such as earnings management.Earnings management is done to create a good image of the company's financial statement, so investors will not gain negative opinions about the company and will be interested in making investment.Therefore, investors need some education, so they will not take wrong actions in their investment activities in the stock exchange.The objective of the research was to find out and analyze the factors which influenced the management of manufacturing companies of food and drink listed in the Indonesia Stock Exchange in the period 2013-2016 by examining and analyzing the influence of the proportion of independent commissariat board, auditing committee, institutional ownership, firm size, leverage, and profitability with quality as the controlling variable auditing on earnings management.The population was all manufacturing of food and drink companies listed in Indonesian Stock Exchange in the period 2013-2016 with a total of 16 companies.There were 11 companies from each year in this period taken as the samples by employing purposive sampling technique, so there were 44 companies in total that were analyzed by applying multiple linear regression analysis models.The hypothesis was tested by using Test and f Test.Based on the suggestion from previous researchice, this researchContributed by addingindependentvariables;namely,profitability, firm size and leverageonearnings management with resultsdemonstratedthat institutional ownership and firm sizehad a positive andsignificant influence on earnings management while leverage by proxy in the debt to equity ratio had a negative and significant influence on the earnings management with auditing quality as the controlling variableinthemanufacturing companiesoffood anddrink listed in the Indonesia Stock Exchange forthe period 2013 to 2016.